PENINGKATAN EFEKTIFITAS BELAJAR SISWA PADA MATERI TOLAK PELURU DENGAN MEDIA MODIFIKASI BOLA PLASTIK DI KELAS VI SD NEGERI 011 PULAU MUNGKUR KECAMATAN GUNUNG TOAR KABUPATEN KUANTAN SINGINGI - Suryaningsih, Evita (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2018)
This research dilator by the results of learning to reject the bullet of grade VI SD Negeri 011 Pulau MungkurGunung Toar is still very low. This study aims to improve learning outcomes Physical education and studenthealth. From the data analysis there is an increase of both teacher activity, student activity, and student learningresult, that is teacher activity in meeting 1 cycle I the percentage is 60% with enough category and secondmeeting is obtained 76% good category while in cycle II there is increasing percentage of teacher activity from88% to 92%. Viewed from the student activity also increased from the meeting 1 cycle I was 56% with thecategory less and the second meeting obtained 72% enough category whereas in cycle II there was an increaseof student activity percentage from 88% to 92%. Judging from the result of student learning before action orClassroom Action Research was conducted by 5 (29,4%) complete students, after classroom action research wasconducted on cycle 1 complete student to 12 people (70,5%), while in cycle 2 to 15 people (88.2%). The increasein the average score of the basic score of cycle 1 was increased by 15 points and from cycle I of cycle 2 therewas an increase of 13 points. From the data analysis there is an increase both from teacher activity, studentactivity, and student learning outcomes. It can be concluded that the application of plastic ball modificationmedia can improve learning outcomes Physical education and health of students in grade VI SD Negeri 011Pulau Mungkur Gunung Toar.